2003
DOI: 10.1034/j.1600-0420.2003.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Oculometric features of hyperopia in children with accommodative refractive esotropia

Abstract: ABSTRACT.Purpose: To determine the nature of hyperopia in children with accommodative refractive esotropia (ARE) by evaluating the relationships between corneal radius (CR), axial length (AL), age and equivalent spherical refraction (SEQ). Methods: A total of 112 children with ARE were included in the study. The children underwent an overall ophthalmic examination including cycloplegic refraction, keratometry and ultrasonic AL measurement. Results: Statistical analysis revealed a strong relationship between AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…10,11 Attempts to estimate axial length in phakic adults also have not utilized the correlation between cycloplegic refraction and axial length/corneal radius ratio and also have had limited accuracy. 14,15 The ratio of axial length to corneal radius seems to maintain a strong inverse correlation to cycloplegic refraction in otherwise normal eyes, with myopia up to À14 D and hyperopia up to 110 D. [4][5][6][7][8][9] However, when hyperopia exceeds approximately 110 D, the correlation no longer holds. 7 All patients in this study had hyperopia \ 18.25 D (as do most patients with refractive accommodative esotropia).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…10,11 Attempts to estimate axial length in phakic adults also have not utilized the correlation between cycloplegic refraction and axial length/corneal radius ratio and also have had limited accuracy. 14,15 The ratio of axial length to corneal radius seems to maintain a strong inverse correlation to cycloplegic refraction in otherwise normal eyes, with myopia up to À14 D and hyperopia up to 110 D. [4][5][6][7][8][9] However, when hyperopia exceeds approximately 110 D, the correlation no longer holds. 7 All patients in this study had hyperopia \ 18.25 D (as do most patients with refractive accommodative esotropia).…”
Section: Discussionmentioning
confidence: 92%
“…3 In phakic eyes, however, there exists a negative correlation between refraction and the ratio of axial length to the corneal radius; in fact, this ratio is the single strongest correlate to cycloplegic refraction. [4][5][6][7][8][9] The use of this correlation could potentially allow estimation of axial length from refraction and keratometry alone without knowledge of crystalline lens power. To the best of my knowledge, this has not been previously described.…”
mentioning
confidence: 99%
“…These findings suggest that axial length has a predominant role in determining hyperopia in amblyopic eyes, similarly to non‐amblyopic hyperopic eyes. Previous studies in non‐amblyopic eyes have found that hyperopia is predominantly axial in nature 49,50 …”
Section: Discussionmentioning
confidence: 99%
“…Other authors have found AE to persist into adolescence and early adulthood (Repka et al 1989). This may be because hyperopia is predominantly axial in nature in children with AE (Uretmen et al 2003). According to Lambert et al (2003), the discontinuing of hyperopic glasses was initiated at a mean age of 8.0 ± 1.1 years.…”
Section: Discussionmentioning
confidence: 99%